Case Fatality Rate and Some Demographic Characteristics Among Children in Al- Elwyia Pediatric Teaching Hospital During Influnza Pandemic 2009 - Raham , Tareef Fadhil; Al-Azzawi , Dawood Salman Hameed; Al-Timimi , Mohammed Farhood (Diyala Journal of Medicine, 2019)
Background: Influenza A (H1N1) virus is the subtype of influenza A virus that was the most common cause of human influenza (flu) in 2009. Other strains of H1N1 are endemic in pigs (swine influenza) and in birds (avian influenza). In June 2009, the World Health Organization declared the new strain of swine-origin H1N1 as a pandemic. This strain is often called swine flu by the public media. Aim : This study was designed to know case fatality rate and some demographic characters during 2009 influnza pandemic among children in Al- Elwyia teaching hospital Baghdad Iraq. Methods : Cross sectional study of 342 cases with signs and symptoms of influenza were studied. Samples were tested with real time polymerase chain reaction (PCR) . Results :Case fatality rate was estimated to be 0.5% . Males and the age group of 6-12years age group are predominantly affected with pandemic influenza. Conclusion : Pediatric H1N1 case fatality rate is comparable to national and global case fatality rate.